Pengaruh Kuat Arus Dan Waktu Kontak Pada Proses Elektrokoagulasi Menggunakan Sel Al-Al Dengan Ketebalan 1 mm Untuk Penyisihan TDS Dari Limbah Cair Lumpur Bor - Apriyanto, Apriyanto; Daud, Syarfi; MS, Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Liquid waste of the drilling mud is a waste that requires processing before it is released into the environment. Direct discharges to the environment especially to river may cause a risk in the water. Electrocoagulation is one of the alternative methods for wastewater treatment. Electrocoagulation is an electrochemical method for water treatment where on the anode occur the release of active coagulant in the form of metal ions while on the cathode electrolysis reaction occurs which release of hydrogen gas. In this electrocoagulation research the sample use liquid waste of drilling mud PT CPI Duri with TDS value 12.390-14.910 mg/L and pH 7,37-7,98. The research was conducted by batch systems. The electrode that used is Aluminum with size 20 cm x 10 cm x 1 mm. The variations used are electric currents (1, 2, 3, 4, 5 A) and contact time (15, 30, 45, 60, 75 min). Result of the research with treatment of contact time 45 minutes and the electric current of 5 A is the most effective treatment to reduce TDS from 14.800 mg/L to be 10.490 mg/L or reduce by 29,12% and the highest pH increase from 7,38 to be 8,76 or increase by 18,7% at treatment with a contact time of 75 minutes and the electric current of 4 A.Key words : Electrocoagulation, TDS, Aluminium Electroda, Batch System.